The Implications of the Political Situation in the UK for Firms: A Bourdieusian Perspective. (28th February 2020) - Śliwa, Martyna; Kerr, Ron; Robinson, Sarah
Abstract: The political situation in the UK poses unprecedented challenges for firms as well as management and organization studies (MOS) scholars. In this short paper, we encourage MOS researchers to consider the French sociologist Pierre Bourdieu's conceptual framework, in particular, his key concepts of field, capital, habitus and hysteresis, as a lens to analyse the multifaceted implications for firms of the current political circumstances in the UK. We explain how a Bourdieusian perspective can help researchers challenge taken‐for‐granted assumptions about the interconnections between politics and business in the context of Brexit and can assist in generating valuable insights regarding the situation of firms operating in the UK in the context of the present changes in the environment.